Consensus diagnostic criteria and monitoring of twin anemia–polycythemia sequence: Delphi procedure. (1st September 2020) - Khalil, A.; Gordijn, S.; Ganzevoort, W.; Thilaganathan, B.; Johnson, A.; Baschat, A. A.; Hecher, K.; Reed, K.; Lewi, L.; Deprest, J.; Oepkes, D.; Lopriore, E.
ABSTRACT: Objectives: Twin anemia–polycythemia sequence (TAPS) is associated with increased perinatal morbidity and mortality. Inconsistencies in the diagnostic criteria for TAPS exist, which hinder the ability to establish robust evidence‐based management or monitoring protocols. The main aim of this study was to determine, by expert consensus using a Delphi procedure, the key diagnostic features and optimal monitoring approach for TAPS. Methods: A Delphi process was conducted among an international panel of experts on TAPS. Panel members were provided with a list of literature‐based parameters for diagnosing and monitoring TAPS. They were asked to rate the importance of the parameters on a five‐point Likert scale. Consensus was sought to determine the cut‐off values for accepted parameters, as well as parameters used in the monitoring of and assessment of outcome in twin pregnancy complicated by TAPS. Results: A total of 132 experts were approached. Fifty experts joined the first round, of whom 33 (66%) completed all three rounds. There was agreement that the monitoring interval for the development of TAPS should be every 2 weeks and that the severity should be assessed antenatally using a classification system based on middle cerebral artery (MCA) peak systolic velocity (PSV), but there was no agreement on the gestational age at which to start monitoring. Once the diagnosis of TAPS is made, monitoring should be scheduled weekly. For the antenatal diagnosis of TAPS, the combination of MCA‐PSV ≥ 1.5 MoM in the anemic twin and ≤ 0.8 MoM in the polycythemic twin was agreed. Alternatively, MCA‐PSV discordance ≥ 1 MoM can be used to diagnose TAPS. Postnatally, hemoglobin difference ≥ 8 g/dL and intertwin reticulocyte ratio ≥ 1.7 were agreed criteria for diagnosis of TAPS. There was no agreement on the cut‐off of MCA‐PSV or its discordance for prenatal intervention. The panel agreed on prioritizing perinatal and long‐term survival outcomes in follow‐up studies. Conclusions: Consensus‐based diagnostic features of TAPS, as well as cut‐off values for the parameters involved, were agreed upon by a panel of experts. Future studies are needed to validate these diagnostic features before they can be used in clinical trials of interventions. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.